1996
DOI: 10.1111/j.1540-8191.1996.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgery in Nonagenarians

Abstract: Cardiac surgery in carefully selected nonagenarians is justified and can be performed with acceptable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Operative mortality and morbidity rates were reportedly acceptable, but previous series were limited by the number of cases 5,7,8,10,11 or by the lack of follow-up data. 9 Therefore, the information currently available is still insufficient to draw definitive conclusions and to guide clinical practice.…”
Section: Clinical Perspective On P 213mentioning
confidence: 99%
“…Operative mortality and morbidity rates were reportedly acceptable, but previous series were limited by the number of cases 5,7,8,10,11 or by the lack of follow-up data. 9 Therefore, the information currently available is still insufficient to draw definitive conclusions and to guide clinical practice.…”
Section: Clinical Perspective On P 213mentioning
confidence: 99%
“…Many previous studies have demonstrated that cardiac surgery can be performed with acceptable results not only in octogenarians, but also in nonagenarians. [9][10][11] However, it is well known that advanced age is a risk factor for mortality, and elderly patients are more likely to suffer from postoperative complications. 2,3,8,9) Bridges, et al reported from the Society of Thoracic Surgeons National Database with a total of 662033 patients that operative mortality was 11.8% for patients more than 90 years of age, 7.1% for those 80 to 89 years, and 2.8% for those 50 to 79 years and the incidence of renal failure and prolonged ventilation was highest among patients more than 90 years of age (9.2% and 12.2%), compared with those 80 to 89 years (7.7% and 10.5%) or 50 to 79 years (3.5% and 6.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Three reports [8,10,13] from a single institution covered overlapping time periods and could not be collated, so the largest series was chosen [10] . It was possible to combine the data in 2 reports from another centre [9,11] . Two papers dealt with outcomes in nonagenarian patients covering 2 different time periods at the same institution [14,19] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twelve single-centre series of nonagenarians were identified [8][9][10][11][12][13][14][15][16][17][18][19] . Three reports [8,10,13] from a single institution covered overlapping time periods and could not be collated, so the largest series was chosen [10] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation